The effect of vibration cycle ergometry on pulmonary VO2 kinetics, isokinetic knee torque, and lower extremity explosive power - Kramer, M.; Kholvadia, A. (Ergonomics, 2021)
Whole-body vibration training is useful for eliciting additional training benefits, but whether vibration-based cycle ergometry would elicit similar benefits has been largely unexplored. Thirteen participants were recruited to investigate differences in vibration (VB) cycle ergometry compared to non-vibration (NV) cycle ergometry with regards to oxygen uptake (VO2) kinetics, rating of perceived exertion (RPE), heart rate (HR), jumping height, and isokinetic knee joint torque at different intensities and cadences. Meaningful ergometer differences (in favour of VB) were evident for maximal steady state VO2 HR and RPE, but not for the phase II VO2 time constant. No meaningful changes were observed for jumping height or isokinetic knee joint torque. The noteworthy increases in VO2, RPE and HR when using VB ergometry, specifically at higher cadences, and independent of intensity domain, may be linked to changes in muscle fibre recruitment or muscle activation.